The warren buffett way - Hagstrom, Robert G (Random House, lnc, 2004)
A decade has passed since the book that introduced Warren Buffett to the world - The Warren Buffett Way by Robert Hagstrom - first appeared. Since then, Buffett has solidified his reputation as the greatest investor of all time - quietly amassing a multibillion-dollar fortune, despite the wild fluctuation of the markets